The thrombotic risk of spaceflight: has a serious problem been overlooked for more than half of a century?. (19th May 2020) - Limper, Ulrich; Tank, Jens; Ahnert, Tobias; Maegele, Marc; Grottke, Oliver; Hein, Marc; Jordan, Jens
Abstract: The first ever venous thrombotic condition associated with spaceflight, an internal jugular vein thrombus requiring anticoagulation, has recently been reported. Systematic investigation of space travel-associated thrombotic risk has not been conducted. Cellular, animal, and human studies performed in ground-based models and in actual weightlessness revealed influences of weightlessness and gravity on the blood coagulation system. However, human study populations were small and limited to highly selected participants. Evidence in individuals with medical conditions and older persons is lacking. Evidence for thrombotic risk in spaceflight is unsatisfactory. This issue deserves further study in heterogeneous, high risk populations to find prevention strategies and to enable safe governmental and touristic human spaceflight.